Foreign Presence and Industrial Concentration In Indonesian Food Industries - Dahlia Nauly; Harianto Harianto; Sri Hartoyo; Tanti Novianti (Signifikan: Jurnal Ilmu Ekonomi, 2020)
Indonesia requires foreign investment to meet the capital needs of the food industries. On the other hand, foreign presence can cause high industrial concentration. This paper analyzes the effect of foreign presence on the concentration of the food industry in Indonesia using panel data from 28 subsectors in the period 2011-2015. The data used is the annual Large and Medium Industries Survey (IBS) data from Statistics Indonesia. The concentration indicators used are the concentration ratio (CR4) and the Herfindahl Hirschman Index (HHI). By using panel regression, the result shows that foreign presence has a positive influence on the concentration of the food industry in Indonesia. Besides, the economies of scale and market size also significantly influence the concentration of the food industry. The result indicates that the government investment policy must endorse more competition among firms.JEL Classification Code: L66, L16 How to Cite:Nauly, D., Harianto., Hartoyo, S., & Novianti, T. (2020). Foreign Presence and Industrial Concentration in Indonesian Food Industry. Signifikan: Jurnal Ilmu Ekonomi, Vol. 9(1), 69-80. doi: http://dx.doi.org/10.15408/sjie.v9i1.12200.